Comparison of Insulin Resistance and β-Cell Dysfunction Between the Young and the Elderly in Normal Glucose Tolerance and Prediabetes Population: A Prospective Study - Chen, G.; Shi, L.; Cai, L.; Lin, W.; Huang, H.; Liang, J.; Li, L.; Lin, L.; Tang, K.; Chen, L.; Lu, J.; Bi, Y.; Wang, W.; Ning, G.; Wen, J. (Hormone and Metabolic Research, 2017)
Insulin resistance and β-cell function are different between the young and elderly diabetes individuals, which are not well elaborated in the nondiabetic persons. The aims of this study were to compare insulin resistance and β-cell function between young and old adults from normal glucose tolerance (NGT) to prediabetes [which was subdivided into isolated impaired fasting glucose (i-IFG), isolated impaired glucose tolerance (i-IGT), and a combination of both (IFG/IGT)], and compare the prevalence of diabetes mellitus (DM) in the above prediabetes subgroups between different age groups after 3 years. A total of 1 374 subjects aged below 40 or above 60 years old with NGT or prediabetes were finally included in this study. Insulin resistance and β-cell function from homeostasis model assessment (HOMA) and interactive, 24-variable homeostatic model of assessment (iHOMA2) were compared between different age groups. The rate of transition to diabetes between different age groups in all pre-diabetes subgroups was also compared. Compared with the old groups, young i-IFG and IFG/IGT groups exhibit higher log HOMA-IR and log HOMA2-S, whereas the young i-IGT groups experienced comparable log HOMA-IR and log HOMA2-S when compared with old i-IFG and IFG/IGT groups. Three prediabetes subgroups all had similar log HOMA-B and log HOMA2-B between different age groups. In addition, the prevalence of diabetes in young i-IFG was statistically higher than that in old i-IFG after 3 years. Age is negatively related to log HOMA2-B in both age groups. Considering an age-related deterioration of β-cell function, young i-IFG, young i-IGT, and young IFG/IGT all suffered a greater impairment in insulin secretion than the old groups. Young i-IFG and IFG/IGT have more severe insulin resistance than the old groups. In addition, young i-IFG characterized with a higher incidence of DM than the old i-IFG. These disparities highlight that the prevention to slow progression from prediabetes to type 2 diabetes should be additionally focused in young prediabetes individuals, especially young i-IFG.
Keywords: insulin resistance; β-cell function; prediabetic; young and old adult; normal glucose tolerance